Designing an On-Demand Printing Service Platform: Validating a User-Centered Interface to Empower MSMEs in the Instant Economy Era - Elvan Putra Pratama Ramanovanda; Yoga Putra Pratama (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2025)
The on-demand economy has transformed consumer expectations, demanding fast, transparent, and efficient services. However, the MSME printing sector in Indonesia is often still hampered by manual processes that cannot meet these demands. This research aims to design and validate an on-demand printing service platform interface that acts as a digital bridge between customer demand and MSME production capacity. Using a User-Centered Design (UCD) methodology, a high-fidelity interactive prototype was designed and validated through usability testing with 20 respondents. The test results demonstrated excellent usability, with an average task completion rate of 93%, an overall relative efficiency of 91.4%, and a user satisfaction score of 88%. These results validate that the platform design focusing on instant ordering flows, real-time price calculation, and a job management dashboard for service providers successfully creates an effective and satisfying user experience. The implication of this research is a validated platform model that can serve as a catalyst for printing MSMEs to adapt to the on-demand economy, increase their competitiveness, and participate in the broader digital ecosystem.